An examination on legal issues in Islamic home financing : a focus on Al-Bay Bithaman 'Ajil (Abba) / Muhammad Ghiyathuddin Abdul Halim, Huzaimi Hashim, Muhammad Effendy Ahmad - Abdul Halim, Muhammad Ghiyathuddin; Hashim, Huzaimi; Ahmad, Muhammad Effendy (2011)
The rapid development of Islamic finance throughout the world has brought about positive changes in Malaysia's financial services industry. Beginning with the establishment of a full-fledged Islamic bank, Bank Islam Malaysia Berhad, following the coming into force of the country's very first own Islamic banking law, ie Islamic Banking Act 1983, that year heralded the dawn of a new services sector in the country which has seen to date the setting up of other 20 full-fledged Islamic banks as well as more inclusive participation by conventional banks in the Islamic banking scheme. Together with the Central Bank of Malaysia Act 2009, Banking and Financial Institutions Act 1989, Takaful Act 1984 and the Securities Commission (Amendment) Act 2007, these governing laws under the auspices of Bank Negara Malaysia and Securities Commission of Malaysia formed the legal framework required in providing an enabling environment that attracts, encourages and spurs on continued progress of the Islamic banking and financial services, domestically as well as cross-border. Such rapid progress that Malaysia has been enjoying should not be hampered by several legal issues that still persistent in beleaguering Islamic banking transactions, particularly involving the Al-Bay Bithaman 'Ajil facilities. Still the most sought-after due to its relatively widest availability in the market, this financing product is increasingly losing customers' confidence due to perennial court proceedings involving the product on the ground that it contains elements prohibited by Islamic law. In this regard, this paper aims at examining the legal issues, which have been causing disputes over the compliance of the product to Sharfah, and also the governing laws as well as incidental laws so as to analyse the interactions and consistencies between one another. In so far as the legal issues are analysed, this paper will suggest recommendations which, be it not the most viable as it may, seek for the increase in number of Islamic finance specialised courts which have been outnumbered by piles of disputes, the adoption of equity-based financing facilities which are fairer than that of debt-based, and the amendments to relevant laws and resolutions that have yet to show complete consistencies in their interactions between one another and with Sharfah principles.